Benign clear cell "sugar" tumor of the lung in a patient with Birt-Hogg-Dubé syndrome: a case report. Issue 1 (December 2016) - Gunji-Niitsu, Yoko; Kumasaka, Toshio; Kitamura, Shigehiro; Hoshika, Yoshito; Hayashi, Takuo; Tokuda, Hitoshi; Morita, Riichiro; Kobayashi, Etsuko; Mitani, Keiko; Kikkawa, Mika; Takahashi, Kazuhisa; Seyama, Kuniaki
Abstract Background Birt-Hogg-Dubé (BHD) syndrome is a rare inherited autosomal genodermatosis and caused by germline mutation of thefolliculin (FLCN ) gene, a tumor suppressor gene of which protein product is involved in mechanistic target of rapamycin (mTOR) signaling pathway regulating cell growth and metabolism. Clinical manifestations in BHD syndrome is characterized by fibrofolliculomas of the skin, pulmonary cysts with or without spontaneous pneumothorax, and renal neoplasms. There has been no pulmonary neoplasm reported in BHD syndrome, although the condition is due to deleterious sequence variants in a tumor suppressor gene. Here we report, for the first time to our knowledge, a patient with BHD syndrome who was complicated with a clear cell "sugar" tumor (CCST) of the lung, a benign tumor belonging to perivascular epithelioid cell tumors (PEComas) with frequent causative relation totuberous sclerosis complex 1 (TSC1 ) or2 (TSC2 ) gene. Case presentation In a 38-year-old Asian woman, two well-circumscribed nodules in the left lung and multiple thin-walled, irregularly shaped cysts on the basal and medial area of the lungs were disclosed by chest roentgenogram and computer-assisted tomography (CT) during a preoperative survey for a bilateral faucial tonsillectomy. Analysis of the resected tumor showed large polygonal cells with clear cytoplasm proliferating in a solid pattern. Immunohistochemistry revealed that these tumor cells were positive for microphthalmia-transcription factor, S100, and CD1a but negative for HMB45, indicating that the tumor was a CCST. Genetic testing indicated that the patient had a germline mutation on exon 12 of theFLCN gene, i.e., insertion of 7 nucleotides (CCACCCT) (c.1347_1353dupCCACCCT). Direct sequencing of theFLCN exon 12 using genomic DNA obtained from her microdissected CCST cells clearly revealed loss of the wild-typeFLCN sequence, which confirmed complete functional loss of theFLCN gene. On the other hand, no loss of heterozygosity aroundTCS1 - orTSC2 -associated genetic region was demonstrated. Conclusion To our knowledge, this is the first report of CCST of the lung in a patient with BHDS, indicating that CCST should be added to the spectrum of pulmonary manifestations of BHDS.